Tantangan Komunikasi, Kepercayaan, dan Kebutuhan Emosional pada Pasangan Long Distance Marriage - Sri Rezky Suci Ramadani; Lusiana Safitri; Syafira Aulia; Naila Hanin Tsurayya; Dian Novita Siswanti; Eka Sufartianinsih Jafar (CV. ITTC INDONESIA, 2026)
Long distance marriage (LDM) is a marital condition characterized by geographical separation between partners for a certain period. This situation creates various challenges, particularly in communication, trust, and emotional needs fulfillment. This study aims to comprehensively examine the challenges faced by couples in LDM through a literature review approach. The method used is a literature study analyzing 30 relevant scientific articles published within the last ten years. The findings indicate that communication is the most dominant factor in maintaining relationship harmony, where frequent and open communication enhances intimacy and reduces conflict. Trust also plays a crucial role as the foundation for maintaining commitment, especially in long-distance conditions. Emotional needs such as security, closeness, and support are often not fully met in LDM, leading to feelings of loneliness and anxiety. However, couples can still maintain a harmonious relationship through effective communication, strong commitment, and adaptive coping strategies. Therefore, the success of LDM depends not on physical distance but on the quality of the relationship maintained by the couple.